Inside a house that is haunted : a rebus read-along story - Capucilli, Alyssa Satin, 1957-; Arnold, Tedd (New York : Scholastic, 1998)
A cumulative rhyme in which the spider, ghost, cat, and other inhabitants of a haunted house wake up and startle each other.
"Cartwheel books."
Keywords: Rebuses; Haunted houses -- Fiction; Monsters -- Fiction; Halloween -- Fiction; Stories in rhyme; Rebuses